2016
DOI: 10.1177/2042098616667304
|View full text |Cite
|
Sign up to set email alerts
|

Tiotropium formulations and safety: a network meta-analysis

Abstract: Tiotropium is now delivered two different inhaler devices: the original Handihaler 18 μg once daily, which uses a powder formulation; and the newer Respimat Soft Mist Inhaler (SMI) 5 μg once daily. It has been questioned whether the two devices can be assumed to have the same safety profile, although the TIOSPIR trial showed that tiotropium when administered Respimat SMI 5 μg is not less safe than Handihaler 18 μg. Therefore, we have carried out a safety evaluation of tiotropium Handihaler 18 µg tiotropium Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 76 publications
0
16
0
1
Order By: Relevance
“…Finally, but not less important, also the drug formulations and the characteristics of the specific devices, that can influence the systemic drug concentrations, may have an impact on the possible occurrence of cardiovascular SAEs, and lead to potential imbalance of the safety profile in favor of some LABA/LAMA FDCs rather than others. 78 , 79 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, but not less important, also the drug formulations and the characteristics of the specific devices, that can influence the systemic drug concentrations, may have an impact on the possible occurrence of cardiovascular SAEs, and lead to potential imbalance of the safety profile in favor of some LABA/LAMA FDCs rather than others. 78 , 79 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the probability that each intervention arm was the most effective than the others was calculated by counting the proportion of iterations of the chain in which each intervention arm had the highest mean difference, and the surface under the cumulative ranking curve (SUCRA), representing the summary of these probabilities, was also calculated. The SUCRA is 100% when a treatment is certain to be the best, and 0% when a treatment is certain to be the worst [31,38].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of bias for the impact of xanthines on lung function and their safety profile in stable COPD patients was assessed via the consistency/inconsistency analysis to check whether the outcomes resulting from the consistency and inconsistency models fit adequately with the line of equality, as previously described [19]. Furthermore, the inconsistency of evidence was also assessed by quantifying the inconsistency factor, indicating whether one of the treatment had a different effect when it was compared with the others [20].…”
Section: Study Selectionmentioning
confidence: 99%
“…It should be taken into account that, although the massive TIOSPIR (Tiotropium Safety and Performance in Respimat) trial showed that tiotropium administered via Respimat ® 5 mg is not less safe than Handihaler ® 18 mg [74], it has been suggested that the administration of tiotropium via Respimat ® should be avoided in patients with pre-existing cardiovascular comorbidities [75]. Nevertheless, a recent meta-analysis concerning the safety profile comparison between tiotropium Respimat ® and tiotropium Handihaler ® performed on more than 43,000 COPD patients, suggests that all the possible effort should be carried out proactively identify patients at increased risk of cardiovascular adverse events when treated with tiotropium or another antimuscarinic drug, independently by the inhaler device [76].…”
Section: Soft Mist Inhalermentioning
confidence: 99%